Electricity Power, Democratic Governance and Economic Growth: Evidence from Nigeria - Maji, Ibrahim Kabiru; Wazirib, Salisu Ibrahim (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
The study examines the impact of democratic governance and corruption on electricity power supply in Nigeria. To achieve this goal, an integrated regression analysis such as Dynamic Ordinary Least Squares (DOLS), Fully Modified OLS, Canonical Cointegrating Regression and OLS were utilized to estimate data spanning the period of 1986 – 2020. The result revealed a negative and significant impact of democracy and corruption on electricity power generation in Nigeria. On the other hand, economic growth has shown a positive and important impact on electricity generation, suggesting that higher GDP growth will increase the supply of electricity in Nigeria. The implication of this findings are as follows: (i) one of the dividends of democracy which is providing public good to the citizens have not been achieved, as such, policymakers need to give more attention to the provision electricity supply; (ii) the institutions in charge of fighting corruption such as the Economic and Financial Crime Commissions (EFCC) need to be further strengthened in Nigeria.